2017
DOI: 10.1096/fj.201601168r
|View full text |Cite
|
Sign up to set email alerts
|

Viruses comprise an extensive pool of mobile genetic elements in eukaryote cell cultures and human clinical samples

Abstract: Viruses shape a diversity of ecosystems by modulating their microbial, eukaryotic, or plant host metabolism. The complexity of virus-host interaction networks is progressively fathomed by novel metagenomic approaches. By using a novel metagenomic method, we explored the virome in mammalian cell cultures and clinical samples to identify an extensive pool of mobile genetic elements in all of these ecosystems. Despite aseptic treatment, cell cultures harbored extensive and diverse phage populations with a high ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 86 publications
1
38
0
Order By: Relevance
“…The transcytosis of bacteriophages across confluent epithelial cell layers ( Fig. 1 ) provides a mechanistic explanation for the occurrence of phages within the human body in the absence of disease ( 8 10 , 12 , 13 ) and supports the establishment of the intrabody phageome ( 35 ). Apical-to-basal transcytosis was observed with every phage type investigated across diverse cell lines ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…The transcytosis of bacteriophages across confluent epithelial cell layers ( Fig. 1 ) provides a mechanistic explanation for the occurrence of phages within the human body in the absence of disease ( 8 10 , 12 , 13 ) and supports the establishment of the intrabody phageome ( 35 ). Apical-to-basal transcytosis was observed with every phage type investigated across diverse cell lines ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Phages are detected in blood or serum rarely or never, because of the low density of phages in these samples. Further confirmation of the translocation and immunomodulating hypothesis has recently been provided by Thannesberger et al [ 36 ], who—using novel metagenomic approaches—showed the presence of phages in urine of healthy individuals as well as patients. Therefore, by translocating from the gut to other tissues phages may mediate their immunomodulating functions not only locally in the intestinal tract, but also at other sites of the mammalian organism.…”
Section: Phage Translocation and Potential Implications Of This Phenomentioning
confidence: 80%
“…Shotgun libraries for Illumina MiSeq sequencing were prepared with the NEBNext ® Ultra II DNA Library Prep Kit for Illumina ® in combination with the Index Primer Set 1 (NEB, Frankfurt, Germany) according to manufacturer’s instructions and as described in (57). Briefly, 500 ng of dsDNA were randomly fragmented by ultrasonication in a microTUBE on a M220 Focused-ultrasonicator™ (Covaris, USA) in a total volume of 130 μl 1xTE for 80 seconds with 200 cycles per burst (140 peak incident power, 10% duty factor).…”
Section: Methodsmentioning
confidence: 99%